A Case Study of S-Curve Analysis: Causes, Effects, Tracing and Monitoring Project Extension of Time - Mohamad, Habib Musa; Mohamad, Mohamad Ibrahim; Saad, Ismail; Bolong, Nurmin; Mustazama, J.; Mohd Razali, Siti Nooraiin (Civil Engineering Journal, 2021)
S-Curve analysis in the construction interpreted as managing project with knowledge and traceable in the context of sustainable construction while displays the cumulative costs, labour hours or other quantities plotted against time. In the contract administration, delays in completing a construction project led to the breach of contract but, in contracts itself allow the construction period to be extended where there are delays that are not the contractor's fault. Under those circumstances, a presentation of a case-study regarding the analysis of S-Curve of a life project drew comparative interpretation of project performance towards project delivery schedule has been conducted in private initiative project. This study aims to investigate and examine the factors that cause delays in construction projects from the perspective of S-curve representations. The paper aims to provide in depth light about the existing causes of project delay and describe the key sources of financing problem and identify the consequences of contraventions of contract. Two distinct parts divided which are refers to the methods used to assess the perceptions of clients, consultants, and contractors on the relative importance of causes of delay in a project and referred to the procurement and documentation to analyse the delay. As a result, an Extension of Time (EOT) granted and identically changed the progress towards extension time where better planning demanded for improvement and restoration progress kept on track. This paper presented a practical and comparative S-Curve within extension of time to ensure delivery of project on schedule. In the long run, the identified causes are combined into 16 factors. Finally, the result of this match was brought in order to critically understand and provide a guideline to contractor in preparing EOT application and choose reliable factor based on the specific circumstances of project delay factors thorough review conducted to reveal the nature of EOT application techniques.Â Doi: 10.28991/cej-2021-03091679 Full Text: PDF